Differences in habitat use between the native Eurasian beaver and the invasive North American beaver in Finland - Alakoski Riikka; Kauhala Kaarina; Selonen Vesa (Springer International Publishing, 2022)
Habitat requirements largely determine the distribution and abundance of a species. An invasive species can therefore threaten the survival of a native species, if the two species are similar in niche use. In Finland, the distribution of the invasive North American beaver (Castor canadensis) is approaching the range of the native Eurasian beaver (Castor fiber) possibly creating a threat for the latter. We compared the habitat use of the native and invasive beaver species in Finland in the main distribution of the species and within a smaller area where the species live in sympatry. We compared the used habitats (volume of birch and other deciduous trees and distance to agricultural and urban areas) at beaver lodges and at random locations in the available riparian habitat with (conditional) logistic regression models. Results indicated that the native beaver lodges were located closer to agriculture than those of the invasive beaver. The volume of birch was also slightly greater near the lodges of the native beaver than those of the invasive beaver. However, habitat use of both of the species seemed quite flexible, because the habitat near lodges did not differ much from the available habitat. We conclude that the probability that the North American beaver will invade the distribution area of the Eurasian beaver in Finland depends, at least partly, on the ability of the former to live in proximity to agricultural areas. However, methods other than those related to managing habitat quality may be the best approach to controlling the invasive species.